Modeling and Experimental Verification of an Electromagnetic and Piezoelectric Hybrid Energy Harvester - Yuanyuan, Fan; Yingjun, Sang; Man, Li; Shangguang, Wu; Zujun, Ding; Yeqin, Wang; Yunrong, Hao (Journal of Engineering and Technological Sciences, 2016)
This paper describes mathematical models of an electromagnetic and piezoelectric hybrid energy harvesting system and provides an analysis of the relationship between the resonance frequency and the configuration parameters of the system. An electromagnetic and piezoelectric energy harvesting device was designed and the experimental results showed good agreement with the analytical results. The maximum load power of the hybrid energy harvesting system achieved 4.25 mW at a resonant frequency of 18 Hz when the acceleration was 0.7 g, which is an increase of 15% compared with the 3.62 mW achieved by a single electromagnetic technique.